USE DIAGONALIZATION TO RAISE O MATRIX TO A HIGH POWER - Meliyeva , M.; Ergashev , F. (Scientific practical conference, 2025)
This thesis discusses the method of using diagonalization to raise a matrix to a high power. Diagonalization provides an efficient way to simplify complex computations, especially for large matrices. The process of powering a diagonal matrix and reconstructing the original matrix is explained. Practical examples are presented to demonstrate the advantages of the method.